A proposed English studies programme for the new certificate-in-education course at the Teacher's Training College, Singapore - Sobrielo, Amy 1938- (s.n.], 1972)
This study examined the existing English Studies Syllabuses for the Certificate-in-Education Full-Time General Course (English Medium) and the English Studies Syllabuses for the Higher School Certificate Holders Course (English Medium). Both these courses are being offered by the Teachers' Training College, Singapore.